The V-RAMP program: Building research administration and management capacity in Nigeria - Muktar H. Aliyu; Zubairu Iliyasu; Donna J. Ingles; Holly M. Cassell; Wendy H. Lloyd; Aima A. Ahonkhai; Aliyu Abdu; Carolyn M. Audet; C. William Wester (Inishmore Laser Scientific Publishing Ltd, 2021)
The increasing volume and complexity of research activities in Nigeria necessitates urgent measures to improve research infrastructure in grants administration and management. The **V**anderbilt-Nigeria **R**esearch **A**dministration and **M**anagement Training **P**rogram (V-RAMP) seeks to build infrastructure capacity in research administration and management and research ethics at a major teaching hospital in Nigeria. We will perform a mixed methods needs assessment of the administrative and management environment and develop an action plan to address infrastructure needs, prioritize processes, and guide program implementation. We will capacitate a newly established Office of Research Administration and improve the knowledge and skills of research administrators and grant managers via short term in-person trainings in Nashville, Tennessee and in Kano, Nigeria and through remote learning opportunities. We will enhance local administrative efficiency and performance of research ethics operations through training and mentoring of members and staff of the ethics review committee. Systematic processes to streamline protocols, including a Research Electronic Data Capture (REDCap) protocol tracking database and standard operating procedures in the responsible conduct of research and rigor and reproducibility will also be developed. V-RAMP will enable the creation of a high-quality research administration environment that is knowledgeable, efficient, and compliant regarding the fiscal, management and ethical standards of sponsored research.